Plasmodium attenuation: connecting the dots between early immune responses and malaria disease severity - Fernandes, Priyanka; Frank, Roland; Lewis, Matthew D.; Mueller, Ann-Kristin (Frontiers in Microbiology, 2014)
Sterile attenuation of Plasmodium parasites at the liver-stage either by irradiation or genetic modification, or at the blood-stage by chemoprophylaxis, has been shown to induce immune responses that can protect against subsequent wild-type infection. However, following certain interventions, parasite attenuation can be incomplete or non-sterile. Instead parasites are rendered developmentally stunted but still capable of establishing an acute infection. In experiments involving Plasmodium berghei ANKA, a model of experimental cerebral malaria, it has been observed that several forms of attenuated parasites do not induce cerebral pathology. In this perspective we collect evidence from studies on murine malaria in particular, and attempt to “connect the dots” between early immune responses and protection from severe cerebral disease, highlighting potential parallels to human infection.